2018
DOI: 10.1371/journal.pone.0200662
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of mental health care workers' constructions about culturally and linguistically diverse people

Abstract: A systematic review of research published in English was conducted across seven electronic databases in psychology, health and social sciences. The aim was to ascertain the nature of mental health care workers’ constructions about culturally and linguistically diverse individuals in order to facilitate provision of culturally appropriate service delivery and multicultural training. The constructs and perspectives of 5,870 mental health workers with regards to minority populations are represented across the 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 61 publications
(127 reference statements)
0
17
1
Order By: Relevance
“…2 CARES model of therapeutic alliance the United States [15]. Discussions about race and ethnic dynamics have been taking place in the United States for over 500 years, compared to Australia whose national engagement in such debates is relatively recent (about 150 years) [12,15,21,43,44]. As such, missing from Australian discourses is a clearer understanding of how mental health care practitioners respond to their own and societal construing of non-White clients within a sociocultural context of Whiteness and what this means for practitioner engagement in culturally competent practice and their ability to effectively support a therapeutic alliance with non-White clients.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…2 CARES model of therapeutic alliance the United States [15]. Discussions about race and ethnic dynamics have been taking place in the United States for over 500 years, compared to Australia whose national engagement in such debates is relatively recent (about 150 years) [12,15,21,43,44]. As such, missing from Australian discourses is a clearer understanding of how mental health care practitioners respond to their own and societal construing of non-White clients within a sociocultural context of Whiteness and what this means for practitioner engagement in culturally competent practice and their ability to effectively support a therapeutic alliance with non-White clients.…”
Section: Safetymentioning
confidence: 99%
“…In Australia, there is a dearth of research investigating how mental health practitioners construe and respond to their construing of non-White and White clients. Our recent systematic review [ 15 ], which included 5,870 mental health practitioners, demonstrated that constructions about non-White people are intimately linked to workers’ perceived ability to be culturally competent and supportive of an effective therapeutic alliance. The review highlighted that little is known about the impact of construing about non-White people on the strategies that practitioners employ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The preliminary search used ProQuest Central to identify the key words contained in study titles and abstracts and to ascertain index terms used to describe articles. Following Dune, Caputi, and Walker (2018), a stepby-step search strategy was employed (see Figure 1). Pertinent key words were discussed, expanded upon, and refined by the primary researchers.…”
Section: Search Strategymentioning
confidence: 99%